Effect of litter size on post-weaning growth of Iberian piglets - Duarte J.L.; Izquierdo M.; Bazán J.; Ayuso D.; Hernández F.I.; Corral J.M.; García Casco J.M. (7th International Symposium on the Mediterranean Pig, 2012)
The current Iberian pig breeding program genetically evaluates sires and dams for 30-day and 90-day weight traits. However, very few studies relating the effect of litter size on piglet weight and growth have been published for this breed. Therefore, this study evaluates the effect of litter size on piglet weight and growth. Data consisted of 6,300 individual weights of piglets from the data-base of the Iberian Pig Association (AECERIBER) and belonging to 4 commercial herds. Weights were standardized to 30, 60, 90 and 120 days, and pre-and post-weaning average daily gains were calculated. The General Linear Model Procedures of SAS were used for data analysis, including the following fixed effects: herd and farrowing season; piglet sex; and litter size at birth, at 24 hours and at weaning. Piglet growth patterns from birth to 120 days were described. Litter size significantly affected these weights, although the effect of the increase in litter size was not constant, except in the case of birth weight. Perinatal mortality was greater in large litter sizes.
7. International Symposium on the Mediterranean Pig, 2010/10/14-16, Córdoba (Spain)